2021
DOI: 10.1111/dme.14567
|View full text |Cite
|
Sign up to set email alerts
|

‘I was ready for it at the beginning’: Parent experiences with early introduction of continuous glucose monitoring following their child's Type 1 diabetes diagnosis

Abstract: Aim: This study aimed to capture the experience of parents of youth with recent onset Type 1 diabetes who initiated use of continuous glucose monitoring (CGM) technology soon after diagnosis, which is a new practice. Methods: Focus groups and individual interviews were conducted with parents of youth with Type 1 diabetes who had early initiation of CGM as part of a new clinical protocol. Interviewers used a semi-structured interview guide to elicit feedback and experiences with starting CGM within 30 days of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
(68 reference statements)
1
31
1
Order By: Relevance
“…Alarm fatigue has been identified as a common reason for discontinuing with rtCGM use 29 . However, recent qualitative studies of rtCGM use, including this study, have not identified alarm fatigue 15–18 . This may be due to the short duration of CGM use in these studies.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Alarm fatigue has been identified as a common reason for discontinuing with rtCGM use 29 . However, recent qualitative studies of rtCGM use, including this study, have not identified alarm fatigue 15–18 . This may be due to the short duration of CGM use in these studies.…”
Section: Discussioncontrasting
confidence: 60%
“…However, this improvement came with the added responsibility of continually monitoring and taking action. Parents reported improved sleep due to reduced need for nocturnal glucose monitoring in a similar manner to Buckhardt et al 15 and Tanenbaum et al 18 Given the negative impacts of disturbed sleep, 4 it was not surprising that the possibility of sleep without disruption—should glucose alarms not be triggered—was highly valued by parents. In this respect, while nighttimes were improved by DIYrtCGM, the requirement for ‘eternal vigilance’ (Sullivan‐Boyani et al 3 , p. 27) was increased during waking hours.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations